Anti Acne Vulgaris Topical Cream From Combination Extract of Gymnanthemum Amygdalinum Del. and Elaeis Guineensis Jacq. Leaves - Dian Ika Perbina; Wahyudi; Ayu Syahfitri; Berkat Waruwu , Syukur (Talenta Publisher, 2020)
Acne is one problem in adolescents and adults who can reduce self-confidence. This study aimed to formulate the combination cream of African leaf extract and palm oil leaves to determine the antibacterial activity of African leaf extract against several acne-causing bacteria (Propionibacterium acne and Staphylococcus epidermidis). Test antibacterial activity of extracts and cream with disc diffusion method. The cream is made with concentration of 5, 10 and 20% w/w. The evaluation results of cream with concentration of 5, 10 and 20% were physically stable for 4 weeks of storage at temperature room, homogeneous, pH and it did not cause irritation. Based on the test results, a combination of African leaf extract with concentration of 5% effectively inhibited bacterial growth with an average inhibition zone diameter of 12.06 mm for Propionibacterium acne bacteria and 13.63 mm for Staphylococcus epidermidis bacteria. The result of this study suggest that combination of African leaf extract and palm leaves posses potent anti-bacterial activity against Propionibacterium acne and Staphylococcus epidermidis.